2001
DOI: 10.1542/peds.107.3.485
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Suicide Attempts: Risks and Protectors

Abstract: In these national samples of black, Hispanic, and white youth, unique and cross-cutting factors derived from a resiliency framework predicted or protected against attempting suicide. In addition to risk reduction, promotion of protective factors may offer an effective approach to primary as well as secondary prevention of adolescent suicidal behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
513
6
23

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 654 publications
(581 citation statements)
references
References 41 publications
39
513
6
23
Order By: Relevance
“…Our finding that knowledge of self-harm by a friend was strongly associated with DSH for both genders lends support to previous studies pointing to the contagion of suicidal behaviour (Borowsky et al, 2001, Marusic et al, 2004. The strong association we found between DSH and knowledge of DSH in a friend was also reported by other CASE study centres in Australia (De Leo and Heller, 2004) and the UK (Hawton et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that knowledge of self-harm by a friend was strongly associated with DSH for both genders lends support to previous studies pointing to the contagion of suicidal behaviour (Borowsky et al, 2001, Marusic et al, 2004. The strong association we found between DSH and knowledge of DSH in a friend was also reported by other CASE study centres in Australia (De Leo and Heller, 2004) and the UK (Hawton et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…This finding complicates research on the effects of religion on adolescent health and safety risk factors, which generally finds protective effects of religious involvement and conservative religious groups Hill et al 2009;Dew et al 2008;Manglos 2013;Adamczyk and Felson 2012;Adamczyk and Palmer 2008;Wallace and Forman 1998;Harker 2001;Borowsky, Ireland, and Resnick 2001;Regnerus 2003). This study also adds to a growing body of research showing the importance of religious subcultures for life chances and the unfavorable influence of conservative Protestantism and conservative religious beliefs for a number of outcomes, extending this literature to the arena of an important health and safety risk factor (Cline and Ferraro 2006;Darnell and Sherkat 1997;Fitzgerald and Glass 2008;Glass and Jacobs 2005;Keister 2008;Massengill 2008;Sherkat and Darnell 1999;Emerson and Smith 2000;Ellison, Burr, and Mccall 2003;Sherkat 2010Sherkat , 2012Stroope, Franzen, and Uecker 2015;Uecker 2014;Lehrer 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research on adolescents suggests a strong link between violence involving other persons and self-directed violence 1–10. Previous studies have reported a comparatively high prevalence of comorbid self-directed and interpersonal violence among youth in the United States (U.S.) and in Africa 2–4,8,9,11–12.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the current study is to examine early alcohol use initiation, prior to age 13, as a specific risk factor associated with co-occurring suicidal and violent behaviors among a nationally representative sample of boys and girls in the U.S. Other factors that have been associated with violence or suicidal behaviors, either empirically or theoretically, in earlier studies and that are available within the Youth Risk Behavior Survey were included as potential confounders (ie, sadness, low academic grades, binge drinking, weapon carrying, and drug use 1,10,27,28. The current study will determine the role of early alcohol use initiation in the comorbidity of self-directed and interpersonal violence and findings can be used to guide prevention and intervention programs.…”
Section: Introductionmentioning
confidence: 99%